Clinical characteristics for conservative therapy of pediatric parapharyngeal abscesses - Bi,Jing (2021)
Abstract Introduction The role of surgical drainage versus conservative therapy in treating patients with parapharyngeal abscesses is still a theme of debate. Objectives This study aimed to investigate the characteristics associated with good outcomes in pediatric patients with parapharyngeal abscesses treated with conservative therapy. Methods This retrospective chart review was performed on children aged 0.3-14 years with the diagnosis of parapharyngeal abscesses confirmed by computed tomography from January 2013 to March 2018. Patients with a severe upper airway obstruction required early intervention, while those in a stable condition initially received conservative therapy with antibiotics. If the patients appeared unlikely to recover, additional surgical drainage was provided. Multivariate logistic regression models were constructed to investigate the clinical characteristics associated with a good response to conservative therapy. A receiver operating characteristic curve was used to identify the age and abscess size cutoff for predicting a successful response. Results A total of 48 children were included in the study. Patient age, antecedent illness, and abscess size were significantly associated with a response to therapy (Odds Ratio = 1.326, 2.314 and 1.235, respectively). The age cutoff associated with the conservative therapy was 4.2 years (76.9% sensitivity, 68.2% specificity), and the abscess size cutoff associated with the conservative therapy was 23 mm (84.6% sensitivity, 77.3% specificity). Conclusion The findings suggested that younger age, smaller abscess size, and less frequent antecedent illnesses, such as upper respiratory tract infection and lymphadenitis, could predict a successful response to conservative therapy in pediatric patients with parapharyngeal abscesses.